A modified zone model on vertical cable tray fire in a confined compartment in the nuclear power plant. (November 2018) - Huang, Xianjia; Ren, Zhaoying; Zhu, He; Peng, Lan; Cheng, Chihonn; Chow, Wanki
Room fire with vertical cable tray involves upward flame spread along the cable. Assessing the vertical cable tray fire hazard in confined spaces has been challenging because of the strong coupling between flame spread and heat transfer. Long computing time is required in using sophisticated field model with computational fluid dynamics. Therefore, developing an appropriate zone model in a cable room fire with experimental validation is required for engineering applications. In this study, a vertical cable tray fire in a confined compartment was simulated using a modified zone model along three new areas on having temporal variations of the fire position, upward-spreading cable flame considered as a burning source moving at a constant speed, and validated through full-scale experiments on vertical cable tray fire with two typical cable-line spacing. The modified zone model can predict accurately the upper-layer temperature in the compartment. The accuracy is at least 25% higher than the model with fixed fire position. The measured temperature at different heights started to decrease at different times, which was due to the vertical spreading of the cable flame. For interface height, the relative error and normalized Euclidean distance in the time-varying fire position model can be improved by 50%.